Accounting for Racial Differences in Marriage and Employment - Shannon N. Seitz (Queen's University, Department of Economics, 2002)
The extent to which marriage market conditions explain differences in marriage and employment decisions across blacks and whites and across men and women is considered in a dynamic, two-sided model of marriage. The quantity and quality of men and women in the marriage market evolve endogenously over time in the model, and in turn influence the allocation of income within married households and the ease with which single agents attract prospective mates. The parameters of the model are estimated using a panel of young men and women from the U.S. The results highlight the responsiveness of intra-household transfers to changes in marriage market opportunities and the importance of women's options outside marriage in determining the black-white gap in marriage rates. Policy experiments suggest that improving the socio-economic characteristics of blacks and reducing the black-white gap in earnings further decreases the black marriage rate, highlighting the importance of equilibrium effects.
Keywords: J11; J12; J2; D83; 330; Sex Ratio; Equilibrium Search; Intra-Household Allocation; Ehe; Erwerbstätigkeit; Weiße; Schwarze Menschen; Familienökonomik; USA